Lipid nanoparticles in anti-breast cancer drug delivery systems and drug-membrane interactions - How, Chee Wun (2014)
Current anticancer drugs are plagued with lack of sustained effect and poor delivery. Many current studies focus on the use of drug carriers, particularly lipid nanoparticles as new drug delivery systems. In this study, a nanostructured lipid carrier (NLC) was formulated to serve as a carrier for tamoxifen (TAM). The study is also undertaken to determine the drugmembrane interaction through the use of liposomes as a membrane model. Hence, the main objectives of this study are to develop and determine the physicochemical and biological properties of NLC loaded with TAM (TAMNLC), and to determine the interaction between the trimethoxybenzoyl analogue of catechin gallate (TMCG) and lipid membrane. The NLC and TAM-NLC were prepared by high pressure homogenisation method. The lipid phase consisted of hydrogenated palm oil, olive oil and phosphatidylcholine as the lipid phase, while the aqueous phases are polysorbate 80, sorbitol, thimerosal and double-distilled water. The major components in the formulation were carefully chosen based on the absence of cytotoxicity towards a normal cell line (murine fibroblasts, BALB/c 3T3). The physicochemical characteristics of NLC, i.e. particle size, zeta potential (ZP), thermal profile, crystallinity, morphology and stability were assessed by photon correlation spectroscopy (PCS), laser doppler velocimetry, differential scanning calorimetry (DSC), wide-angle X-ray diffractometry (WAXD), transmission electron microscopy (TEM) and spectrophotometry, respectively. The release kinetics of TAM-NLC was determined by the Franz diffusion cell system while its cytotoxicity was determined in vitro on the human breast (MCF-7) and mouse mammary (4T1) cancer cell lines. To determine the drug-membrane interaction, a dried lipid film of 1,2-dipalmitoyl-sn-glycero-3- phosphocholine (DPPC) was used to form liposomes and to entrap TMCG and quinone methide (QM, metabolite of TMCG) separately. The interaction of drug with the model membrane was assessed by DSC, WAXD, smallangle X-ray diffractometry (SAXD) and Fourier-transform infrared (FTIR). The PyMOL software was used to construct the molecular model of drug and membrane interaction.The study showed that hydrogenated palm oil, trilaurin and docosanoic acid were significantly less cytotoxic than palmitin. Since surfactants influenced the physicochemical properties of the NLC, polysorbate 20 and 80 were assessed for use in the NLC formulation. The NLC formulated with polysorbate 80 showed good compatibility with the lipid phase, while polysorbate 20 caused destabilisation of the nanoparticles that resulted in phase separation during storage. With polysorbate 80 as surfactant, the NLCs are relatively spherical, with an average size of 102.8 nm, zeta potential of -30.57 mV, and possessed superior particle surface area to volume ratios. The transition temperature of NLC formulated with polysorbate 80 was 55.85 °C, which was lower than that formulated with polysorbate 20 or unprocessed lipid. The results indicated that NLC formulated with polysorbate 80 is of lower crystallinity and this was confirmed by WAXD. The NLC was also shown to be of low cytotoxicity to BALB/c 3T3 cell line. The NLC incubated with foetal bovine serum-supplemented media did not show increase in particle size, suggesting that its stability is good and practicality for use in intravenous administration. The stability of TAM-NLC was determined by storage at physiological pHs. The formulation is more stable at pH 7.4 (blood pH) even though its ZP was lower compared to pH 2.3 (stomach pH). The release of TAM from TAM-NLC followed first-order kinetics, while showing high cytotoxicity to MCF-7 and 4T1 cell lines with halfminimal inhibitory concentration of 5.56 and 5.19 μg mL-1, respectively. To determine the drug-membrane interaction, TMCG was used as the prodrug model and liposomes as the cell membrane model. The DSC analysis showed that TMCG was incorporated into DPPC membranes and had intercalated in-between the phospholipids molecules while reducing the cooperativity and lowering the transition temperature of the gel to liquidcrystalline phase. In addition, TMCG did not affect the macroscopic bilayer organisation of the liposomes; instead it decreased the thickness of the bilayer by forming an interdigitated gel phase. Quinone methide, the active form of TMCG however, showed limited interaction with the phospholipid bilayer indicating that a superficial interaction had occurred between QM and the phospholipid membrane with a weak gel stabilising effect and decreased hydrogen-bonding pattern of the interfacial region of the phospholipid. These results concur with the molecular dynamics simulation studies, which showed that TMCG was incorporated into the membrane phospholipid palisade while QM was excluded and interacted weakly with the polar portion of the lipid bilayer. In conclusion, the study showed that the optimised NLC formulation with low cytotoxicity is a superior vehicle for encapsulation and carriage of TAM. The TAM-NLC developed in this study showed controlled-released characteristics, good stability at physiological pH with potential for tumour targeting. The study also reinforced the reliability of liposomes as cell membrane models, and TMCG interacts very well with it.